Methodological issues in dynamic capabilities research - a critical review - Eriksson T (EMERALD GROUP PUBLISHING LIMITED, 2022)
Originality/value - This study is a novel contribution towards understanding the methods used in DC research. It introduces the issue of methodological fit into the DC discussion and highlights the methodological aspects that need to be considered and reported in more detail in future research articles. It also has implications on how to conceptualise DC.